7 - ‘Desperados, Druggies and Delinquents’: Devising a Community-based Security Regime to Combat Drug Related Crime - Ettang, Dorcas Oyebisi (Africa Development, 2017)
Drug abuse amongst African youths makes them vulnerable to numerous threats. Many easily succumb to crime and violence. In South Africa, drug abuse is on the rise. In 2012, the World Health Organization reported that 15 per cent of South Africa’s population had a drug problem, giving it a reputation as one of the drug capitals of the world. The South African Depression and Anxiety Group in 2013 notes that illegal drug consumption in South Africa is double the global norm. Situated within national and sub-regional contexts, this article examines the growing drugs threat and links this to insecurity in Kokstad Municipality. Through interviews, the article proposes an appropriate community-based response mechanism to address the causes and effects of drug abuse. Drawing from Human Security and the Conflict Theory of Drug Abuse, community-based responses that prevent and reduce drug induced crime at the grassroots are seen as the way forward.